Diversity and biodeteriorative potential of bacterial isolates from deteriorated modern combined-technique canvas painting - Pavic, Aleksandar; Ilic-Tomic, Tatjana; Pacevski, Aleksandar; Nedeljkovic, Tatjana; Vasiljevic, Branka; Morie, Ivana (International biodeterioration & biodegradation, 2015)
Cultivable bacteria colonizing deteriorated modern painting on canvas were identified in order to evaluate their potential to deteriorate organic and inorganic painting's constituents. Different sampling and cultivation strategies enabled isolation of bacteria belonging to nine genera of Firmicutes, Proteobacteria, and Actinobacteria phyla. Overall predominant bacteria were species of Bacillus (51%) and Staphylococcus (36%) genera. Representatives of six different genera (Staphylococcus, Acinetobacter, Agrococcus, Janibacter, Rhodococcus, and Stenotrophomonas) were isolated for the first time from deteriorated canvas. Almost all isolated bacteria produced proteases, esterases, and lipases, which may be involved in deterioration of painting's binders and media. Bacteria expressing endocellulase were reported. Selected bacterial isolates were tested for ability to deteriorate six pigments. All tested isolates were able to grow in the presence of Ivory black, Red and Yellow ochre, as a sole source of phosphate and iron, inducing their fading. The majority of isolates induced solubilization of Zinc white and Cobalt deep green. Cadmium red pigment that inhibited the growth of a half of isolates proven to be the most toxic pigment. Isolated bacteria were equipped with all required metabolic prerequisites in order to pose a threat to the painting as a whole. •Taxonomic and functional diversity of bacteria from modern painting were examined.•Bacillus sp. and Staphylococcus sp. were predominant bacterial isolates.•Bacteria with endocellulolytic activity were isolated from painting.•In-vitro bacterial interaction with six painting pigments was assessed.•Natural pigments could be source of P and Fe while Cadmium red was the most toxic.